A novel study on separation of particles driven in two steps based on standing surface acoustic waves. (September 2022) - Chen, Xueye; Lv, Honglin; Zhang, Yaolong
Abstract: With the development of surface acoustic wave devices, the separation of micron-sized particles based on standing surface acoustic waves (SSAW) has been studied, and the method has the advantages of high efficiency and ease of operation. In this paper, we design a two steps SSAW-based model for separating three different sizes of particles. The particle with the largest diameter is separated in the first sorting step region, and the remaining two particles are separated in the second sorting step region. During the study, we investigate the SSAW device firstly. We chose three different materials for the comparative analysis of the piezoelectric substrates. Next, we investigate the effects of fork-finger pairs and input voltage of the interdigital transducer (IDT) on the stability of the output waveform and sound pressure intensity. Finally, we select the appropriate number of fork-finger pairs and determine the acoustic pressure intensity in the low and high voltage regions respectively, so that three different particles could be successfully sorted in two steps. This research result can provide a certain theoretical basis for practical research fields such as cell sorting and drug detection.